Values Education, the Family, and Youth in Tajikistan: Building Docile Subjects - Lemon, Edward; Torno, Swetlana; Rashidov, Tuychi (Problems of post-communism, 2025)
This article examines the relationship between youth, the family, and the authoritarian state in Tajikistan. We argue that the state works through both young people and the family in its attempts to produce loyal citizens through values education that focuses on patriotism, national identity, and allegiance to the state. We examine how the government frames this relationship through discourse analysis of 13 speeches by President Emomali Rahmon, an analysis of the content of laws on education and youth, a close reading of the official training program of the course "Family Education," and an ethnographic study of a "Girls' Competition."